Initial GPS scintillation results from CASES receiver at South Pole, Antarctica - Deshpande, K. B.; Bust, G. S.; Clauer, C. R.; Kim, H.; Macon, J. E.; Humphreys, T. E.; Bhatti, J. A.; Musko, S. B.; Crowley, G.; Weatherwax, A. T. (Radio Science, 2012)
Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/94940/1/rds6025.pdf